2010
DOI: 10.1088/0004-637x/713/2/1134
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evolution of Protostellar and Protoplanetary Disks. I. Outbursts

Abstract: As an initial investigation into the long-term evolution of protostellar disks, we explore the conditions required to explain the large outbursts of disk accretion seen in some young stellar objects. We use onedimensional time-dependent disk models with a phenomenological treatment of the magnetorotational instability (MRI) and gravitational torques to follow disk evolution over long timescales. Comparison with our previous two-dimensional disk model calculations (Zhu et al. 2009b indicates that the neglect of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
173
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 45 publications
4
173
2
Order By: Relevance
“…This process remains speculative because detailed physical conditions in the disk, such as viscosity, magnetic field, etc., are unknown. However, we note that these unstabilities may eventually trigger FU Ori outbursts as they propagate inward (Zhu et al 2010;Bae et al 2013), thus potentially making AA Tau a pre-FUOr candidate. Disk instabilities may also trigger dense disk winds (e.g., Lesur et al 2013;Bai & Stone 2013) that may be the source of enhanced lineof-sight extinction if they are able to lift up dust from the disk mid-plane (Owen et al 2011;Bans & Königl 2012).…”
Section: Discussionmentioning
confidence: 89%
“…This process remains speculative because detailed physical conditions in the disk, such as viscosity, magnetic field, etc., are unknown. However, we note that these unstabilities may eventually trigger FU Ori outbursts as they propagate inward (Zhu et al 2010;Bae et al 2013), thus potentially making AA Tau a pre-FUOr candidate. Disk instabilities may also trigger dense disk winds (e.g., Lesur et al 2013;Bai & Stone 2013) that may be the source of enhanced lineof-sight extinction if they are able to lift up dust from the disk mid-plane (Owen et al 2011;Bans & Königl 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Thus the ratios of mass infall rate from outer to inner disc during each outburst is related to the duration of Model presented by Zhu et al (2010) includes an MRI instability contribution to viscosity parameter if the temperature of the disc goes above MRI triggering temperature (T M ) and also includes an effective viscosity contribution from gravitational instability beyond the radius given by Toomre's instability parameter Q. The relation between R limit andṀ in this model is R limit ∝Ṁ 2 9 Thus, τ visc ∝Ṁ > ( 52 21 ) 9 ≈ 3500.…”
Section: Implication On Models Of Outburstmentioning
confidence: 99%
“…The excitation of nonlinear spiral waves by giant planets also plays an important role in structuring protoplanetary disks and in driving the migration of embedded planets (Bryden et al 1999;Kley 1999;Nelson et al 2000). Models for the origin of FU Orionis outbursts have been presented where spiral waves, originating in the gravitationally unstable outer regions of protostellar disks during the early infall phase, propagate into the inner disk regions and trigger the magnetorotational instability (MRI) by heating and ionizing the disk gas there (Gammie 1999;Armitage et al 2001;Zhu et al 2010;Bae et al 2014). Recent work has also shown that the infall of low angular momentum material onto a protostellar disk during the early infall phase can also generate global spiral waves (Lesur et al 2015).…”
Section: Introductionmentioning
confidence: 99%